2011
DOI: 10.5194/cp-7-1327-2011
|View full text |Cite
|
Sign up to set email alerts
|

Past surface temperatures at the NorthGRIP drill site from the difference in firn diffusion of water isotopes

Abstract: Abstract.A new ice core paleothermometer is introduced based on the temperature dependent diffusion of the stable water isotopes in the firn. A new parameter called differential diffusion length is defined as the difference between the diffusion length of the two stable water isotopologues 2 H 1 H 16 O and 1 H 2 18 O. A model treatment of the diffusion process of the firn and the ice is presented along with a method of retrieving the diffusion signal from the ice core record of water isotopes using spectral me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 39 publications
2
52
1
Order By: Relevance
“…The next event of particular interest is the Younger Dryas cooling, when Northern Hemisphere temperatures are thought to have dropped by several degrees at 12.8-11.7 ka and most prominently in high latitudes Heiri et al, 2007;Lea et al, 2003;Liu et al, 2012;Simonsen et al, 2011;Steffensen et al, 2008). The event presents a conceptual paradox; the magnitude of the cooling is difficult to reconcile with rising atmospheric CO 2 (approximately +10 ppm compared to the earlier Bølling period ∼ 14.5 ka; Bereiter et al, 2015) and increasing boreal summer insolation (Berger and Loutre, 1991).…”
Section: Climate Evolution Over the Last Deglaciationmentioning
confidence: 99%
See 1 more Smart Citation
“…The next event of particular interest is the Younger Dryas cooling, when Northern Hemisphere temperatures are thought to have dropped by several degrees at 12.8-11.7 ka and most prominently in high latitudes Heiri et al, 2007;Lea et al, 2003;Liu et al, 2012;Simonsen et al, 2011;Steffensen et al, 2008). The event presents a conceptual paradox; the magnitude of the cooling is difficult to reconcile with rising atmospheric CO 2 (approximately +10 ppm compared to the earlier Bølling period ∼ 14.5 ka; Bereiter et al, 2015) and increasing boreal summer insolation (Berger and Loutre, 1991).…”
Section: Climate Evolution Over the Last Deglaciationmentioning
confidence: 99%
“…Certainly, others have shown that the location of injection is a controlling factor on the impact of freshwater delivery to the ocean, not just laterally (e.g. Condron and Winsor, 2012;Smith and Gregory, 2009), but also in terms of depth (e.g. Roche et al, 2007).…”
Section: Coordinating Further Simulationsmentioning
confidence: 99%
“…The difference in firn diffusion of water isotopes (Johnsen et al, 2000) offers the possibility to estimate past J. Jouzel: A brief history of ice core science over the last 50 yr temperature changes from very detailed δD and δ 18 O profiles in ice cores (Simonsen et al, 2011). Co-isotopic measurements (δD and δ 18 O) have also been applied to study basal ice as a result of the fractionation processes taking place during melting/refreezing processes (Jouzel and Souchez, 1982;Souchez and Jouzel, 1984;Jouzel et al, 1999).…”
Section: Alternative Estimates Of Temperature Changes In Greenland Anmentioning
confidence: 99%
“…The rapid, sub-millennial fluctuations, however, are not present in the model output because of lacking short-timescale forcing variations. Furthermore, the model seems to underestimate the amplitude of the temperature record by approximately 5 K. Some uncertainty resides in the interpretation of the data, as Greenland temperature records inferred from different water isotope data show different glacial-interglacial variability (Kindler et al, 2014;Simonsen et al, 2011). However, most likely this underestimation of temperature variability is predominantly a consequence of the zonal averaging in our model, which distributes temperature anomalies over the entire meridional band.…”
Section: Comparison Of Reconstructed Temperaturesmentioning
confidence: 76%
“…These indicate local temperature variability, although their interpretation is ambiguous (see e.g. different glacial-interglacial reconstructed temperature variability in Kindler et al, 2014, andSimonsen et al, 2011). Greenland and Antarctic climate have been shown to correlate closely to each other (EPICA community members, 2006).…”
Section: Introductionmentioning
confidence: 99%